Frieze Group Pattern in Buyung Dance Formation - Lia Andriani; Arif Muchyidin; Hendri Raharjo (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2020)
Buyung dance is a traditional Sundanese dance that reflects the Sundanese community in taking water. Also, the meaning of a pitcher is a kind of tool made of metal or clay, often used by some village women in earlier times to take water in rivers, lakes, or ponds. When viewed closely, the Buyung dance formation has mathematical concepts such as the field of geometry, transformation of the geometry, and the counts and measurements made by the dancers in performing the Buyung dance. Besides, each formation also has its philosophical significance. This research is a qualitative study. The researcher directly goes to the field, studies a natural process of discovery through the process, records, analyzes, interprets, and reports, and draws conclusions from the process. Data collected through observation, interviews, and documentation. Based on the research, it was concluded that the beauty of the formation in the pitcher dance was identical to the pattern of the Frieze group. also, the formation formed has a philosophical meaning that reflects the local wisdom of the local communityÂ Â